THE EFFECT OF HYPNO BIRTHING ON REDUCING THE ANXIETY OF PREGNANT WOMEN IN THE THIRD TRIMESTER FACING CHILDBIRTH AT THE CLINIC OF MITRA SEHAT MEDICAL CENTER - Ariyani, Ariyani; Kamidah, Kamidah (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: Anxiety in pregnancy is a normal condition that occurs in various circumstances such as labor. Anxiety during pregnancy causes psychological problems that cause fear and anxiety that are embedded in the mother's subconscious mind so that they develop into negative thoughts. Research on anxiety in Indonesia ranges from 28.7% which has an impact on childbirth, the hypnobirthing method can reduce anxiety in pregnant women compared to counseling and health promotion programs. Purpose: This study is to determine the effect of hypnobirthing on reducing the anxiety of third trimester pregnant women facing childbirth Hypnobirthing exercises for pregnant women before childbirth can reduce anxiety and fear before childbirth. Methods: This study used a Pre-experimental design experiment with a one group pretest- posttest design approach. This research was located at the Mitra Sehat Medical Center Clinic, Wawasan Village, Tanjung Sari District, South Lampung Regency from March to April 2024. The population in the study was 25 third trimester pregnant women who experienced anxiety.Non probability sampling technique with total sampling. The results of the study based on the characteristics of respondents who experienced anxiety before hypnobirthing, namely 1 respondent (4%) experienced mild anxiety, 4 respondents (16%) experienced moderate anxiety, and 20 respondents (80%) experienced severe anxiety. The results of the study based on the characteristics of respondents after being given hypnobirthing, namely 7 respondents (28%) became not anxious, 12 respondents (48%) became mildly anxious, and 1 respondent (4%) experienced severe anxiety. Analysis with the Wilcoxon test found Asymp.Sig (2- tailed) worth 0.000 <0.05. Conclusion: there is an effect of hypnobirthing on reducing the anxiety of third trimester pregnant women facing childbirth at the Mitra Sehat Medical Center Clinic.